Anterior Chamber Migration of Dexamethasone Intravitreal Implant (Ozurdex®) through Basal Iridectomy (Ando) in a Pseudophakic Patient. Issue 3 (May 2016) - Stepanov, Alexandr; Codenotti, Marco; Ramoni, Andrea; Prati, Matteo; Jiraskova, Nada; Rozsival, Pavel; Bandello, Francesco
Purpose: Intravitreal implantation of dexamethasone implant (Ozurdex®) is being widely used for the treatment of macular edema (ME) after branch or central retinal vein occlusion, diabetic ME, and persistent ME associated with uveitis or Irvine-Gass syndrome. We describe a complication: migration of the dexamethasone implant into the anterior chamber through basal iridectomy (Ando) in a pseudophakic patient with development of corneal edema and secondary high intraocular pressure. Methods: This is a case report of migration of Ozurdex® through basal iridectomy in a pseudophakic patient with iris claw lens. Conclusions: Pseudophakic patients, with a history of vitrectomy, even those with a basal iridectomy (Ando), are at high risk for migration of the Ozurdex® into the anterior chamber and development of corneal edema.